2013
DOI: 10.1007/s12328-013-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric synovial sarcoma: molecular diagnosis and prediction of prognosis

Abstract: A 42-year-old Japanese woman complained of upper abdominal pain. Endoscopic examination demonstrated an elevated lesion in the body of the stomach, and a biopsy specimen demonstrated proliferation of atypical spindle cells. She underwent partial gastrectomy; the resected tumor measured 3.5 × 2.8 × 1.2 cm in size. Histological examination disclosed the haphazard proliferation of spindle cells in the mucosa mixed with less prominent epithelioglandular component. The spindle cells were positive for cytokeratin, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…GIST should be distinguished from other mesenchymal neoplasms of the gastrointestinal tract. The differential diagnosis includes leiomyoma/leiomyosarcoma, Schwannoma, desmoid tumor, inflammatory myofibroblastic tumor and synovial sarcoma . Neoplastic cells in these tumors usually present spindle morphology.…”
Section: Clinical Practice For Wild Type Gistmentioning
confidence: 99%
“…GIST should be distinguished from other mesenchymal neoplasms of the gastrointestinal tract. The differential diagnosis includes leiomyoma/leiomyosarcoma, Schwannoma, desmoid tumor, inflammatory myofibroblastic tumor and synovial sarcoma . Neoplastic cells in these tumors usually present spindle morphology.…”
Section: Clinical Practice For Wild Type Gistmentioning
confidence: 99%
“…Another difference between these previously reported oesophageal and gastric synovial sarcomas is that the median patient age of the oesophageal cases (25 years) was lower than that of the gastric cases (52 years); the median age of our two gastric synovial sarcoma patients was 42 years. All 13 previously reported gastric synovial sarcomas that were immunostained for CD117 and the single reported duodenal synovial sarcoma were reported not to express the protein . Furthermore, the two gastric cases that had been immunostained for DOG1 were also reported not to show expression of this protein .…”
Section: Discussionmentioning
confidence: 97%
“…It is also noted that both CD117 expression and DOG1 expression by synovial sarcoma arising in soft tissues have been well described . The patient prognoses associated with the previously reported primary gastrointestinal synovial sarcomas varied, but it has been suggested that tumours of larger size and/or with poorer differentiation have a worse outcome…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations